Factors of runoff generation in the Dongting Lake basin based on a SWAT model and implications of recent land cover change. (10th May 2018) - Lotz, Tom; Opp, Christian; He, Xun
Abstract: The Dongting Lake basin in China has been changed substantially by human activity. Environmental issues like land reclamation, land cover change, flood and droughts and the effects of climate change call for a deep understanding of the hydrological system to enable stakeholders to plan mitigation and adaptation strategies. For this study a SWAT model of the watershed was created and calibrated to the runoff of the four main tributaries. The simulated reaction of the computational units (HRU) to rainfall was then linked to the physical attributes that defined the respective HRU to find the main effects of runoff generation. The results showed that surface runoff and Evapotranspiration are mainly determined by land cover under the same rainfall conditions, while interflow and ground water flow also depend on slope angle. Soil effects were minor due to the utilized soil data. Recent land cover change as detected from Landsat scenes of the years 2000 and 2013 has brought an increase in the forested area in the Dongting basin, especially on higher slope inclinations. This increase led to an increase in interflow and ground water flow, slowing down the overall response of the basin to rainfall. This balances the discharge between periods with high and low rainfall and helps to mitigate flood and drought severity. Cross effects between the factors, the size of the research area and the quality of input data were limiting factors of the used method.